The journey of Typhon-Echidna as a binary system through the planetary region - Araujo, R. A.N. [UNESP]; Galiazzo, M. A.; Winter, O. C. [UNESP]; Sfair, R. [UNESP] (Oxford University Press (OUP), 2018)
Among the current population of the 81 known trans-Neptunian binaries (TNBs), only two are in orbits that cross the orbit of Neptune. These are (42355) Typhon-Echidna and (65489) Ceto-Phorcys. In this work, we focused our analyses on the temporal evolution of the Typhon- Echidna binary system through the outer and inner planetary systems. Using numerical integrations of the N-body gravitational problem, we explored the orbital evolutions of 500 clones of Typhon, recording the close encounters of those clones with planets. We then analysed the effects of those encounters on the binary system. It was found that only ≈22 per cent of the encounters with the giant planets were strong enough to disrupt the binary. This binary system has an ≈3.6 per cent probability of reaching the terrestrial planetary region over a time-scale of approximately 5.4Myr. Close encounters of Typhon-Echidna with Earth and Venus were also registered, but the probabilities of such events occurring are low (≈0.4 per cent). The orbital evolution of the system in the past was also investigated. It was found that in the last 100 Myr, Typhon might have spent most of its time as a TNB crossing the orbit of Neptune. Therefore, our study of the Typhon-Echidna orbital evolution illustrates the possibility of large cometary bodies (radii of 76 km for Typhon and 42 km for Echidna) coming from a remote region of the outer Solar system and that might enter the terrestrial planetary region preserving its binarity throughout the journey.
Keywords: Planets and satellites: dynamical evolution and stability